2019
DOI: 10.1523/jneurosci.0876-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Medium Spiny Neurons in the Dorsomedial Striatum Regulate Ethanol-Containing Conditioned Reward Seeking

Abstract: Adenosine 2A receptor (A 2A R)-containing indirect medium spiny neurons (iMSNs) in the dorsomedial striatum (DMS) contribute to reward-seeking behaviors. However, those roles for ethanol-seeking behaviors remain unknown. To investigate ethanol-seeking behaviors, we used an ethanol-containing reward (10% ethanol and 10% sucrose solution; 10E10S). Upon conditioning with 10E10S, mice that initially only preferred 10% sucrose, not 10E10S, showed a stronger preference for 10E10S. Then, we investigated whether the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 57 publications
4
26
0
Order By: Relevance
“…In this study, we found that mice under body weight restriction did not preferably approach and stay in the ethanol zone before the operant conditioning, whereas operant conditioning with ethanolcontaining reward increased the preference toward ethanol zone in the Y-maze. This is consistent with our previous study, which revealed that operant conditioning with an ethanol-containing reward increases the preference for an ethanol-containing solution zone (Hong et al, 2019). Additionally, we found that a single treatment of NHBA reduced this increase in ethanol zone preference, which suggests that ENT1 and A 2A R are associated with the development of ethanol reward behaviors.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this study, we found that mice under body weight restriction did not preferably approach and stay in the ethanol zone before the operant conditioning, whereas operant conditioning with ethanolcontaining reward increased the preference toward ethanol zone in the Y-maze. This is consistent with our previous study, which revealed that operant conditioning with an ethanol-containing reward increases the preference for an ethanol-containing solution zone (Hong et al, 2019). Additionally, we found that a single treatment of NHBA reduced this increase in ethanol zone preference, which suggests that ENT1 and A 2A R are associated with the development of ethanol reward behaviors.…”
Section: Discussionsupporting
confidence: 93%
“…Mice were placed in operant chambers with two interactive nose holes ("active" and "inactive") (Med-Associates, St. Albans, VT) where they poke a single hole for an ethanol-containing reward (10 ml of 10% ethanol and 10% sucrose in tap water per reinforcer, 10E10S). We employed the same schedule for operant conditioning used in our previous research (Hong et al, 2019). Briefly, on the 1st day of magazine training, mice were trained to approach the magazine on a random time schedule with a reward delivered for 30 minutes.…”
Section: Reward-seeking Behavior Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, genetic and pharmacological DLS A 2A R inhibitions maintain sucrose-seeking behaviours (Li et al, 2016;Nam, Hinton, et al, 2013). Consistently, our recent study shows that optogenetic inhibition of A 2A Rexpressing neurons in the DMS and systemic A 2A R inhibition increases the value of ethanol, when A 2A R agonist suppresses ethanol-seeking (Hong, Kang, et al, 2019). Meanwhile, optogenetic DLS A 2A R activation and genetic DMS A 2A R blockade induce goal-directed sucrose-seeking behaviours (Li et al, 2016).…”
Section: F I G U R Esupporting
confidence: 80%
“…On the other hand, recently developed anion-conducting ChR (ACR) increases intracellular Cl − ion for cellular inhibition [50]. Unlike blue light-sensitive inhibitory opsin ACR, NpHR is an orange light-sensitive inhibitory chloride pump [51]. Using different wavelengths of light, thus, ChR and NpHR together enable optical activation and silencing in the same cells [52,53].…”
Section: Cell-and Circuit-specific Neural Manipulationmentioning
confidence: 99%